(untitled) (CIPEEX, 2025)
Muscle hypertrophy refers to the increase in total muscle mass, characterized by a rise in the number of actin and myosin filaments in each muscle fiber. Skeletal muscle is dynamic, maintaining a balance between protein synthesis and breakdown. Physical training stimulates adaptations like strength and hypertrophy, while inactivity leads to muscle atrophy. Magnetic resonance imaging (MRI) has historically been used to assess muscle tissue with high accuracy, but its application is limited to laboratory settings due to high costs and impracticality in clinical environments. To address this, ultrasound has emerged as a viable tool for evaluating muscle areas with high validity. This study aims to determine the validity of intra- and inter-rater ultrasound measurements of rectus femoris muscle thickness. The reproducibility sample size was determined using interclass correlation with a power of 80% and a significance level of 5%, requiring 52 participants. For repeatability, an ANOVA for repeated measures with a power of 95% was used, requiring 86 participants. Ultrasound (Mindray model M6) with a linear probe (6-14 MHz) will measure muscle thickness at 40% of the femur’s length from the proximal region. Skin markings and standardized probe positioning will ensure consistency. Participants will be in a relaxed, dorsal decubitus position during imaging, with water-soluble gel applied to minimize distortion. All visits will take place in an air-conditioned room, supervised by a professional to ensure procedural accuracy.